2020
DOI: 10.1097/md.0000000000022217
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of geriatric nutritional risk index in elderly patients with severe community-acquired pneumonia

Abstract: The geriatric nutritional risk index (GNRI) is associated with the prognosis of many diseases. However, the association between the GNRI and the prognosis of patients aged ≥65 years with severe community-acquired pneumonia (SCAP) has not been studied. We aimed to evaluate the prognostic value of GNRI in elderly SCAP patients. This study retrospectively analyzed the clinical data of 346 patients aged ≥65 years with SCAP from December 2013 to September 2019. Patients were divided into 4 groups by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Six were conducted in Asia, seven each in Europe and North America, and one included people from multiple continents [ 48 ]. Twelve cohorts included people with CAP [ [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] ], one with HAP [ 60 ], none with COVID-19 pneumonia, one with AP [ [61] , [62] , [63] ], three with HCAP or NHCAP [ [64] , [65] , [66] ], five described “pneumonia” only, or included mixed types of pneumonias [ 47 , [67] , [68] , [69] , [70] ]. One of these cohorts published data on two sub-cohorts, one of people with CAP, the other with pneumonia and chronic kidney disease [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six were conducted in Asia, seven each in Europe and North America, and one included people from multiple continents [ 48 ]. Twelve cohorts included people with CAP [ [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] ], one with HAP [ 60 ], none with COVID-19 pneumonia, one with AP [ [61] , [62] , [63] ], three with HCAP or NHCAP [ [64] , [65] , [66] ], five described “pneumonia” only, or included mixed types of pneumonias [ 47 , [67] , [68] , [69] , [70] ]. One of these cohorts published data on two sub-cohorts, one of people with CAP, the other with pneumonia and chronic kidney disease [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 346 older people (mean age 78 years) hospitalised with NHCAP in China, the odds of poor prognosis (death in hospital or automatic discharge due to adverse prognosis) were greater in those with higher BUN (OR 1.06, 95% CI 1.02 to 1.09) in univariate analysis, but not significant in multivariate analysis [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…16 Wei et al reported that GNRI demonstrated superior predictive value for poor prognosis compared with other inflammatory indicators in older patients with severe community-acquired pneumonia (CAP). 17 Nevertheless, the prognostic utility of GNRI in older patients with aspiration pneumonia remains unclear. Therefore, this study aimed to investigate the prognostic utility of GNRI in older patients with aspiration pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…The most effective recommendations for the care of CAP patients are vaccination and case management, according to the World Health Organization (WHO) [ 7 ]. These have been demonstrated to reduce mortality and morbidity, thereby reducing hospital stays [ 7 , 8 ]. Several studies have found that following treatment guidelines and adhering to them reduces morbidity, death, and healthcare expenditures [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…These have been demonstrated to reduce mortality and morbidity, thereby reducing hospital stays [ 7 , 8 ]. Several studies have found that following treatment guidelines and adhering to them reduces morbidity, death, and healthcare expenditures [ 8 , 9 ]. Although guidelines can steer and standardize illness care, their influence on disease outcomes is less quantifiable.…”
Section: Introductionmentioning
confidence: 99%